Identification of suitable qPCR reference genes for the normalization of gene expression in the BL10-mdx and D2-mdx mouse models of Duchenne muscular dystrophy. - Kayleigh Putker; Anne-Fleur Schneider; Davy Van De Vijver; John Hildyard; Annemieke Aartsma-Rus; Maaike van Putten (PLoS ONE)
Duchenne muscular dystrophy (DMD) is an X-linked disorder that is caused by mutations in the DMD gene, leading to progressive muscle wasting and weakness. There is currently no cure for DMD. The BL10-mdx mouse is the most commonly used model in preclinical DMD studies, but it exhibits a mild disease phenotype compared to DMD patients, limiting research translatability. The newer D2-mdx mouse has a more severe phenotype at an early age and may better recapitulate human disease. To compare these mouse models on a transcriptional level with quantitative RT-PCR, stable and reliable reference genes are indispensable. We aimed to evaluate the stability and reliability of a panel of nine candidate reference genes (Actb, Ap3d1, Gapdh, Hmbs, Htatsf1, Pak1ip1, Rpl13a, Sdha and Zfp91) in the gastrocnemius, diaphragm and heart of mice from both strains and their corresponding wild types aged 4 to 52 weeks. Data was analyzed using geNorm, BestKeeper, deltaCt and NormFinder. We found that Htatsf1, Pak1ip1 and Zfp91 are suitable reference genes for normalization of gene expression in dystrophic and healthy mice, regardless of the tissue type or age. In our hands, Actb, Gapdh and Rpl13a were not suitable as reference genes, exhibiting tissue-, age-, or disease specific changes in expression. This study highlights the importance of the selection of suitable reference genes, as their stability can differ between specific experimental setups.